Features Of Forming A Culture Of Ecological Safety - Lobar MUKHTAROVA (Euro Asian Journal Publishing, 2024)
The article identifies cognitive, acmeological, axiological factors in the formation of a culture of environmental safety, the structure and components of environmental safety in the educational environment
Keywords: environmental safety; culture; acmeological; natural history literacy